A NEW VACCINE FOR THE PREVENTION OF THE CERVICAL CANCER - A.G. Gaivoronskaya; M.G. Galitskaya (Union of pediatricians of Russia, 2008)
The article deals with the one of the most urgent problems of the modern world - viral papilloma. As is known, this is the most widely spread sexually transmitted infection. Human papilloma virus is responsible for the development of such a hazardous pathology as cervical cancer. The only method to prevent it is the vaccination against this virus. The authors introduces the new vaccine against the viral papilloma, ensuring protection from the most on cogenous types of viruses.Key words: viral papilloma, cervical cancer, prevention, vaccination.